Transcriptomic Analysis of Cultured Corneal Endothelial Cells as a Validation for Their Use in Cell-Replacement Therapy - Frausto, Ricardo F. (Cell Transplant, 2015)
The corneal endothelium plays a primary role in maintaining corneal homeostasis and clarity, and must be surgically replaced with allogenic donor corneal endothelium in the event of visually significant dysfunction. However, a worldwide shortage of donor corneal tissue has led to a search for alternative sources of transplantable tissue. Cultured human corneal endothelial cells (HCEnC) have been shown to restore corneal clarity in experimental models of corneal endothelial dysfunction in animal models, but characterization of cultured HCEnC remains incomplete. To this end, we utilized next-generation RNA sequencing technology to compare the transcriptomic profile of ex vivo human corneal endothelial cells (evHCEnC) with that of primary HCEnC (pHCEnC) and HCEnC lines, and to determine the utility of cultured and immortalized corneal endothelial cells as models of in vivo corneal endothelium. Multidimensional analyses of the transcriptome datasets demonstrated that primary HCEnC have a closer relationship to evHCEnC than do immortalized HCEnC. Subsequent analyses showed that the majority of the genes specifically expressed in HCEnC (not expressed in ex vivo corneal epithelium or fibroblasts) demonstrated a marked variability of expression in cultured cells compared with evHCEnC. In addition, genes associated with either corneal endothelial cell function or corneal endothelial dystrophies were investigated. Significant differences in gene expression and protein levels were observed in the cultured cells compared with evHCEnC for each of the genes tested except for AGBL1 and LOXHD1, which were not detected by RNA-seq or qPCR. Our transcriptomic analysis suggests that at a molecular level pHCEnC most closely resemble evHCEnC and thus represent the most viable cell culture based therapeutic option for managing corneal endothelial cell dysfunction. Our findings also suggest that investigators should perform an assessment of the entire transcriptome of cultured HCEnC prior to determination of their potential clinical utility for the management of corneal endothelial cell failure.